Imagery training in young swimmers: Effects on the flow state and on performance - Scurati, R.; Michielon, G.; Longo, S.; Invernizzi, P. L. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Imagery training is the ability to develop mental images increasing human performances. Flow is one of the peak moments corresponding to a state of optimal experience that can be measured through the Flow State Scale (FSS) questionnaire related to 9 fundamentals or dimensions (D1 to D9) in which Flow can be subdivided. This study aimed to observe the effects of a specific Imagery training on the Flow and on the swimming performance. METHODS: Sixteen young swimmers volunteered for the study: i. Experimental (13.0±0.53 years, 52.5±6.5 kg, 161±7 cm); ii. Control (13.25±1.04 years, 55.38±7.95 kg, 165±8 cm). Supplementing the swimming training during three weeks, Experimental subjects accomplished a specific mental training on the Imagery based on visualizing three images representing important phases of the front crawl. The FSS questionnaire was filled out by subjects before and after training as well as the performance on 100m front crawl stroke was surveyed. RESULTS: FSS was not repeatable for the D5 and D8 dimensions. In the other dimensions no differences were found in the Control, whereas a significant difference (p<0.05) was noticed in some answers of the Experimental subjects referring to the D3, D6, D7 and D9 dimensions. In the 100m front crawl stroke no differences (p>0.05) were found between Experimental and Control as well as between the pre and post training in the intra-group comparisons. DISCUSSION: The lack of the repeatability in D5 (concentration on the task avoiding distractions) is probably related to the young age of swimmers that could induce difficulties in the concentration. Flow state tends anyway to vary after the Imagery training, in D3 (clarity of targets) and in D6 (sense of control) in particular. Imagery training aided athletes in identifying a specific target in order to increase the motivation in reaching it. The negative trend in D7 (lack of the oneself awareness) and in D9 (the autotelic experience) probably depends on forcing a voluntary execution of the technical movement instead of automatic movements the Imagery training would have induced. An extended training for a longer period and with swimmers of different age is advisable in order to study effects on the swimming performance.